2018
DOI: 10.1177/0038038518767075
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Rituals: Small Conversations about Emotional Distress on Twitter

Abstract: There is growing research interest in the sharing of emotions through social media. Usually centred on 'newsworthy' events and collective 'flows' of emotion, this work is often computationally driven. This article presents an interaction-led analysis of small data from Twitter to illustrate how this kind of intensive focus can 'thicken' claims about emotions, and particularly empathy. Drawing on Goffman's work on ritual, we introduce and then apply the idea of 'empathy rituals' to exchanges about emotional dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 60 publications
(62 reference statements)
0
33
0
1
Order By: Relevance
“…Some studies have briefly acknowledged online etiquette. Brownlie and Shaw's (2019) examination of emotional exchanges in online interactions found that, on Twitter, users disclosed distress without specific details in order to protect their privacy, and their audience offered subtle emotional support that was met with gratitude. Others also pointed out strategies that online users use to avoid loss of face, such as carefully choosing words to sustain harmonious relationships (Fossati 2014).…”
Section: Online Interaction Privacy Management and Social Etiquettementioning
confidence: 99%
“…Some studies have briefly acknowledged online etiquette. Brownlie and Shaw's (2019) examination of emotional exchanges in online interactions found that, on Twitter, users disclosed distress without specific details in order to protect their privacy, and their audience offered subtle emotional support that was met with gratitude. Others also pointed out strategies that online users use to avoid loss of face, such as carefully choosing words to sustain harmonious relationships (Fossati 2014).…”
Section: Online Interaction Privacy Management and Social Etiquettementioning
confidence: 99%
“…Social media platforms have attracted attention for their mobilizing abilities, yet also have affective and emotional implication including fostering a sense of solidarity and emotional engagement within political movements (Papacharissi, 2015) and its important role providing support for people in distress. Brownlie and Shaw (2019) (included in this e-special) investigate public emotion work through everyday exchanges on Twitter. Drawing on Goffman, they analyse interactional practices which include empathy, love and affection.…”
Section: Communities Emotions and Everyday Lifementioning
confidence: 99%
“…Research that analyse Twitter and everyday life studies are a few. Bogers and Björneborn (2013) studied meaningful coincidences in everyday life shared on Twitter; Miller, Davis and Partridge (2019) studied everyday life information experiences on Twitter; Brownlie and Shaw (2019) studied everyday conversations about emotional distress on Twitter; and McGarry et al (2019) analysed the performance of everyday life on social media during Gezi Park protests in Turkey. While these studies focused on digital media, social networking sites or specifically Twitter in users' everyday lives, no study in the literature focuses on Twitter as digital space and observes everyday life on Twitter.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%